2021
DOI: 10.1016/j.isci.2020.101977
|View full text |Cite
|
Sign up to set email alerts
|

Impaired cell-cell communication in the multicellular cyanobacterium Anabaena affects carbon uptake, photosynthesis, and the cell wall

Abstract: HIGHLIGHTS SepJ and Fra septal proteins are key for communication in Anabaena filaments Spatial expression of a regulatory gene is affected when those proteins are missing The transcriptomes of Anabaena wild-type and septal protein mutants were mapped Deletion of those proteins leads to global and specific changes in gene expression

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 59 publications
1
10
0
Order By: Relevance
“…nitrogen deprivation only at a low level. Thus, sepJ is induced approximately 1.5-fold to 2fold under nitrogen deprivation (31)(32)(33), whereas fraC and fraD have been reported to be expressed constitutively (15,33) or induced approximately 2-fold under nitrogen deprivation (32). These observations, together with the rapid response to combined N described here, are consistent with a rapid regulation of the septal junctions by a mechanism of gating, as previously suggested (16), rather than with strong induction/repression mechanisms.…”
Section: Discussionsupporting
confidence: 89%
“…nitrogen deprivation only at a low level. Thus, sepJ is induced approximately 1.5-fold to 2fold under nitrogen deprivation (31)(32)(33), whereas fraC and fraD have been reported to be expressed constitutively (15,33) or induced approximately 2-fold under nitrogen deprivation (32). These observations, together with the rapid response to combined N described here, are consistent with a rapid regulation of the septal junctions by a mechanism of gating, as previously suggested (16), rather than with strong induction/repression mechanisms.…”
Section: Discussionsupporting
confidence: 89%
“…In contrast to the WT, the fraC fraD mutant fixed CO 2 at high levels in spite of being deficient in N 2 fixation. This might be related to an altered regulation of C assimilation as recently observed by transcriptomic analysis ( 35 ), which showed increased expression of genes encoding carbon uptake systems and some photosynthetic components in Anabaena mutants lacking septal proteins, including FraCD. In summary, our results have revealed the metabolic heterogeneity of individual cells and filaments in an Anabaena culture under controlled laboratory conditions, highlighting the interplay between C and N 2 fixation and assimilation, which are highly regulated processes ( 32 ).…”
Section: Discussionmentioning
confidence: 54%
“…These transcriptional changes should be taken with caution because it has recently revealed that plasmid genes may suffer genome rearrangements in mutant strains of Anabaena sp. PCC7120 (Camargo et al, 2021). The expression of seven selected genes belonging to different functional categories was analysed in the EB2770FurC strain related to Anabaena sp.…”
Section: Resultsmentioning
confidence: 99%